2008
DOI: 10.1038/nrg2346
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in autism genetics: on the threshold of a new neurobiology

Abstract: Autism is a heterogeneous syndrome defined by impairments in three core domains: social interaction, language and range of interests. Recent work has led to the identification of several autism susceptibility genes and an increased appreciation of the contribution of de novo and inherited copy number variation. Promising strategies are also being applied to identify common genetic risk variants. Systems biology approaches, including array-based expression profiling, are poised to provide additional insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,399
3
19

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,614 publications
(1,449 citation statements)
references
References 144 publications
28
1,399
3
19
Order By: Relevance
“…However, this unexpected finding may relate to high variability of low-level auditory processing abilities in ASD. We suggest that future studies in ASD should give further consideration on 1) the characteristics of the ASD samples -especially in terms of IQ 21 and age, 2) the nature of the auditory stimuli and complexity of the tasks and 3) the investigation of homogeneous subgroups rather than a heterogeneous broader ASD group might be more helpful to identify the multifarious factors that contribute to RRBs (see also Abrahams and Geschwind, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, this unexpected finding may relate to high variability of low-level auditory processing abilities in ASD. We suggest that future studies in ASD should give further consideration on 1) the characteristics of the ASD samples -especially in terms of IQ 21 and age, 2) the nature of the auditory stimuli and complexity of the tasks and 3) the investigation of homogeneous subgroups rather than a heterogeneous broader ASD group might be more helpful to identify the multifarious factors that contribute to RRBs (see also Abrahams and Geschwind, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Few linkage peaks have been identified and replicated and dense SNP analysis of linkage peaks has not revealed common variation accounting for the linkage signal [17]. Thus, replicated linkage peaks are probably signals for aggregation of RVs.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many developmental disorders are heterogeneous (Abrahams & Geschwind, 2008) and this is a particularly pertinent feature of WS, with cognitive, social, genetic and physical characteristics varying considerably from one individual to the next (Porter & Coltheart, 2005). Porter and Coltheart, (2005) challenged the notion of a "syndrome specific" (Howlin, Davies & Udwin, 1998) WS cognitive profile and suggested that subgroups might exist within WS based on their similarities in cognitive profile.…”
Section: Heterogeneity Of Social Behaviours In Williams Syndromementioning
confidence: 99%